HRM and KM as catalysts of environmental performance: A conceptual framework - Ng, Yin-Kuan; Tan, Peter Sin-Howe; Fong, Chee-Yang; Wong, Choy-Har (2012)
The purpose of this paper is to develop a theoretical framework to investigate the relationships among human resource management (HRM), knowledge management (KM) and environmental performance (EP).Environmental friendly business activities demand high level of human resource competency in terms of knowledge, skills and capabilities in order to better firm performance. This paper serves to establish the link among HRM, KM, and EP to fill the gap in the current literature.The research model is proposed based on reviews of the literature on HR and KM perspectives on environmental management and performance.Both theoretical and practical implications are discussed in this paper.With new knowledge gained on the associations among HRM, KM and EP, manufacturing firm managers can focus their effort and resources on HRM and KM to deliver better environmental management effectiveness.It is anticipated that this paper will contribute towards sustainability development for a better living environment.